2000
DOI: 10.1053/he.2000.6780
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione, lactobionate, and histidine: cryptic inhibitors of matrix metalloproteinases contained in university of wisconsin and histidine/tryptophan/ketoglutarate liver preservation solutions

Abstract: UW solution and HTK solution are both used for cold preservation of liver allografts. Although they are about equally effective, their compositions are very different, and they were formulated using different rationales. The authors recently showed an important role for MMPs in liver preservation injury and consequently postulated that these preservation solutions contain cryptic inhibitors of MMP activity. To determine this possibility, the ability of these solutions to inhibit MMP activity was studied. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
56
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 34 publications
6
56
0
2
Order By: Relevance
“…9,15,16 Experimental and clinical studies have shown that both UW and HTK solutions are effective despite the fact that their compositions are very different and their mechanisms of action are not completely known. 3,17,18,19 The controlled settings of LDLT offer a unique opportunity to study the efficacy of these preservation solutions. In fact, most of the variables found in cadaveric liver donors are not present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,15,16 Experimental and clinical studies have shown that both UW and HTK solutions are effective despite the fact that their compositions are very different and their mechanisms of action are not completely known. 3,17,18,19 The controlled settings of LDLT offer a unique opportunity to study the efficacy of these preservation solutions. In fact, most of the variables found in cadaveric liver donors are not present.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Despite their very different compositions, both solutions seem to be equally effective and safe in the long-term preservation of the cadaveric graft. 3 Previous studies comparing the two solutions in cadaveric liver grafts were not randomized, and the results may have been influenced by different factors. Specifically donor age, past medical history, intensive care stay, clinical conditions at the time of the harvest, and ischemic time [4][5][6] influence the quality of the graft and play a role in the functional recovery of the liver and outcome of the patient.…”
mentioning
confidence: 99%
“…Its formulation was compounded to retard acidosis (histidine), prevent membrane injury (tryptophan), and provide a substrate for energy metabolism (ketoglutarate). 78 Recent studies comparing the effectiveness of the two solutions have shown superior outcomes with the HTK solution when the cold ischemic times were below average. 78,80 On the other hand, with long cold ischemic times, UW seems to represent a better solution for preservation purposes.…”
Section: Liver Preservation and Procurementmentioning
confidence: 99%
“…78 Recent studies comparing the effectiveness of the two solutions have shown superior outcomes with the HTK solution when the cold ischemic times were below average. 78,80 On the other hand, with long cold ischemic times, UW seems to represent a better solution for preservation purposes. 77 …”
Section: Liver Preservation and Procurementmentioning
confidence: 99%
“…[1][2][3][4] SEC are the main targets of cold preservation injury, 5,6 and understanding the mechanisms by which they are injured might provide an avenue to development of improved preservation solutions. Our studies show that cold causes actin disassembly 2 and that this is associated with rounding of the cells 2 and release of matrix metalloproteases (MMPs) into the supernatants of SEC cell cultures. 1,3 Actin disassembly and MMP secretion lead to activation of the cell surface, as shown by increased expression of von Willebrand factor and increased adhesiveness for platelets.…”
mentioning
confidence: 99%